Nursing students' knowledge and attitude toward diabetic ulcer care and their contributing factors in Indonesia - Yunita Sari; Arif Setyo Upoyo; Annas Sumeru; Saldy Yusuf; Haryanto; Nuriya; Agis Taufik (Elsevier, 2022)
Objective: The prevalence of diabetic foot ulcer in Indonesia is far greater than the global prevalence. Nursing students are expected to have good knowledge and positive attitudes regarding diabetic ulcer care in order to deliver high-quality wound care during clinical practice. This study aimed to assess nursing students' knowledge and attitudes toward diabetic ulcer care and to investigate the factors related to them. Methods: A cross-sectional study was conducted on 396 academic and clinical phases in three nursing schools in Indonesia from September 2021 to February 2022. Participants completed a survey including a questionnaire about knowledge and attitudes regarding diabetic ulcer care. The data were analyzed using a Chi-square test and multivariate logistic regression analysis. Results: The results show that 43.2% (171/396) of nursing students had inadequate knowledge of diabetic ulcer care. However, 88.9% (352/396) had a favorable attitude toward the topic. Nursing students lacked knowledge about the characteristics of diabetic ulcers, diabetic neuropathy, wound infection, and adjunctive therapy for diabetic ulcers, and many of them believe that diabetic ulcer care is too time-consuming to carry out. Students in the clinical phase of their studies had significantly better knowledge than those in the academic phase (aOR = 9.99, 95% CI 4.96-20.08, P < 0.001). Male nursing students were significantly less likely to have positive attitude toward the topic than female students (aOR = 0.42, 95% CI 0.19-0.96, P = 0.048), and students accustomed to sharing with peers as a source of knowledge had better attitudes than those who were not (aOR = 2.76, 95% CI 1.40-5.41, P = 0.003). Conclusion: Findings show that almost half of the nursing students have insufficient knowledge of diabetic ulcer care. Curriculum developers and educators need to improve the curriculum regarding diabetic wound care and provide strategic programs to improve students' knowledge and attitudes based on the factors discovered in this study.